Do Incentives Matter for the Diffusion of Financial Knowledge? Experimental Evidence from Uganda. (30th May 2018) - Sseruyange, John; Bulte, Erwin
Abstract: Many development interventions involve training of beneficiaries, based on the assumption that knowledge and skills will spread 'automatically' among a wider target population. However, diffusion of knowledge or innovations can be slow and incomplete. We use a randomised field experiment in Uganda to assess the impact of providing incentives for knowledge diffusion, and pay trained individuals a fee if they share knowledge obtained during a financial literacy training. Our main results are that incentives increase knowledge sharing, and that it may be cost-effective to provide such incentives. We also document an absence of assortative matching in the social learning process.